Effects of Dietary Copper Supplementation on Laying Performance, Egg Quality and Plasma Cholesterol Fractions in Laying Ducks - Fouad, A.M.; Li, Y.; Chen, W.; Ruan, D.; Wang, S.; Xie, W.G.; Lin, Y.C.; Zheng, C.T. (Pakistan Journal of Nutrition, 2016)
This study was designed to investigate the influences of dietary copper (Cu) on laying performance, egg quality, plasma total cholesterol (TC), high-density lipoprotein cholesterol (HDLC) and low density lipoprotein-cholesterol (LDLC) concentrations in Shanma laying ducks. A total of 504 egg laying ducks aged 17 week were randomly allotted to seven groups (twelve ducks per replicate and six replicates each treatment). The control group was fed a corn-soybean meal diet, whereas the treatment groups were fed corn-soybean meal diets supplemented with 4, 8, 12, 16, 20, or 24 mg Cu-sulfate/kg. Egg production, egg weight, egg mass, feed conversion ratio, broken egg rate, abnormal egg rate, Haugh unit, yolk color, albumen height, eggshell weight, eggshell percent, eggshell breaking strength, eggshell thickness, plasma TC, HDLC and LDLC concentrations did not appear response to dietary Cu levels. Our results indicated that corn-soybean meal diet containing sufficient amount of Cu for laying performance and egg quality in laying ducks under the conditions of current experiment. Also, laying performance, plasma TC, HDLC, LDLC concentrations and egg quality were not sensitive traits to low levels of Cu.